2013
DOI: 10.1155/2013/360190
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Progranulin Concentrations Are Increased in Patients with Type 2 Diabetes and Obesity and Correlated with Insulin Resistance

Abstract: Insulin resistance (IR) is considered to be one of the most important pathogenesis of glycolipid metabolism disorders. However, the molecular mechanism responsible for IR is not fully understood. Recently, the chronic inflammation has been proposed to be involved in the pathogenesis of IR. In this study, we aim to investigate the concentrations of plasma progranulin in Chinese patients with obesity (OB) and type 2 diabetes mellitus (T2DM), and its relationship to IR. Plasma progranulin concentrations were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 20 publications
4
96
3
1
Order By: Relevance
“…3 Proteolytic cleavage of this precursor protein by extracellular proteases gives rise to smaller peptide fragments termed granulins (GRNs) or epithelins. 5,6,34 Consistent with previous evidences implicating the aggressive inflammation and insulin resistance, 9,11,14 we demonstrated that PGRN treatment led to the attenuated insulin signaling and ER stress, which, in turn, contributes to insulin resistance and relates with inflammation. 35,36 However, the normal function of PGRN is complex, with intact PGRN having anti-inflammatory properties, whereas GRNs have been shown to promote inflammation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3 Proteolytic cleavage of this precursor protein by extracellular proteases gives rise to smaller peptide fragments termed granulins (GRNs) or epithelins. 5,6,34 Consistent with previous evidences implicating the aggressive inflammation and insulin resistance, 9,11,14 we demonstrated that PGRN treatment led to the attenuated insulin signaling and ER stress, which, in turn, contributes to insulin resistance and relates with inflammation. 35,36 However, the normal function of PGRN is complex, with intact PGRN having anti-inflammatory properties, whereas GRNs have been shown to promote inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…7 Moreover, circulating PGRN is significantly higher in clinical subjects with type 2 diabetes and positively correlated with macrophage infiltration in omental adipose tissue. 9,11,12 In particular, PGRN is more highly expressed in visceral adipose tissue of the insulin-resistant patients with morbid obesity than in their age-, sex-and BMI-matched insulin-sensitive counterparts. [13][14][15] Thus, PGRN may be an important modulator in a variety of glucose and energy regulation with specific effect on target tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of the secreted protein progranulin in the central nervous system (CNS) causes neurodegeneration: the neurodegenerative disease frontotemporal dementia (FTD, see glossary) with partial progranulin deficiency and neuronal ceroid lipofuscinoisis with total deficiency [1] . In peripheral tissues, progranulin excess is linked to obesity and insulin resistance [2, 3] (Figure 1). It is unclear how alterations in progranulin levels result in such diverse disease mechanisms.…”
Section: A Progranulin Primermentioning
confidence: 99%
“…Progranulin levels were reported to be higher in subjects with obesity [9,10,15], type 2 diabetes [10,15] or insulin resistance [16]. In addition, progranulin levels decline during long-term weight loss intervention [17].…”
mentioning
confidence: 99%